Corrective Radial and Ulnar Osteotomies for Distal Radial Fracture Malunion - Wada, Takuro (JBJS Essent Surg Tech, 2012)
INTRODUCTION: We describe a technique consisting of simultaneous radial closing-wedge and ulnar shortening osteotomy to treat malunion of distal radial fractures. STEP 1: PREOPERATIVE PLANNING: Plan the radial closing-wedge osteotomy to correct the volar tilt angle to 8.5° to 15.5° and the ulnar shortening osteotomy to restore ulnar variance to −2.5 to 0.5 mm. [Figure: see text] STEP 2: RADIAL CLOSING-WEDGE OSTEOTOMY: Remove the wedge of bone from the radius and reduce the distal fragment, keeping the dorsal cortex as a hinge. [Figure: see text] [Figure: see text] [Figure: see text] STEP 3: DISTAL ULNAR SHORTENING OSTEOTOMY: Resect the section of the ulna equivalent to the positive ulnar variance with transverse osteotomies. [Figure: see text] [Figure: see text] STEP 4: PLATE FIXATION OF THE RADIAL OSTEOTOMY SITE: Hold together the two fragments of the radius with a Kirschner wire and fix the osteotomy site with a volar locking plate. [Figure: see text] STEP 5: PROXIMAL ULNAR SHORTENING OSTEOTOMY: Evaluate residual ulnar positive variance with fluoroscopy and restore the ulnar variance to within a normal range by removing additional bone from the proximal fragment. [Figure: see text] [Figure: see text] STEP 6: PLATE FIXATION OF THE ULNAR OSTEOTOMY SITE: Use a compression device to close and fix the ulnar osteotomy site. [Figure: see text] STEP 7: POSTOPERATIVE MANAGEMENT: Allow early motion immediately after the operation. RESULTS: We retrospectively evaluated forty-two patients at a minimum of one year after treatment of an extra-articular distal radial malunion with a radial corrective osteotomy. WHAT TO WATCH FOR: Indications Contraindications Pitfalls & Challenges